Trends in Islamic Revisionist Discourse on Qur'anic Studies (A Critical Analysis of John Wansbrough's Thought) - Supandi, Muhammad Diaz; Agustono, Ihwan (Jurnal Kawakib, 2024)
The following paper discusses the trend in modern revisionist discourse about Qur'ānic studies with the critical engagement of John Wansbrough's idea. Known for his historical and literary criticism, Wansbrough claimed that the Qur'an was a product of Jewish and Christian traditions, and its canonization is of much later origin than that which is ascribed to the time of the Prophet Muhammad. While influential, this thesis has been criticized as an attack on the authenticity of the Qur'ān. This paper looks at the methodology and arguments of Wansbrough in light of scholars such as Fazlur Rahman, who question the assumptions of revisionism. Through qualitative library-based research, this paper highlights some of the methodological flaws in Wansbrough's approach and proposes alternatives that are in tune with Qur'ānic studies. The findings raise the need to respond to such criticisms if misinterpretations so rife in current Qurānic discourses are to be averted. This is a research contribution to the ongoing scholarly conversation on revisionist methodologies and textual interpretation in Qur'ānic studies.